The Relationship Between Education and the Environment: A Critical and Nonviolent Perspective - Rigoni Grabar, Paola; Mancarella, Dino (In Factis Pax: Journal of Peace Education and Social Justice, 2025)
The relationship between education and the environment has undergone various historical phases, as exemplified by practices such as open-air schools and forest schools. These educational approaches emphasize the significance of learning in natural contexts to foster a dialectical relationship between theory and practice, a core characteristic of experiential learning. Such practices offer a response to contemporary environmental challenges by proposing a non-competitive and nonviolent interaction with the environment, integrating the needs of human life with the preservation of ecosystems. However, these perspectives often conflict with current educational systems, which tend to be neutral or subordinate to dominant economic and political dynamics. Traditional pedagogy frequently neglects the role of the teacher’s personal experience as an integral component of the educational process, favoring detached and abstract approaches. This paper instead advocates for an engaged pedagogy, wherein the educator’s experience becomes both educational content and a tool for transformation. The nonviolent dimension of educational practice emerges as a process of conscientization, bridging theory and practice, and driven by engagement with what lies outside school buildings and beyond the certainties imposed by an education system often subservient to a neoliberal economy. This economy, by projecting human existence into an artificial and abstract dimension, has contributed to a loss of connection with reality. Neoliberalism has promoted consumption as the solution to existential crises, distancing humans from the authentic needs of the natural and animal environment. From this critical perspective, education must reclaim its transformative role, abandoning subordination to the market and reorienting itself toward a practice that fosters critical, nonviolent awareness. Such an approach is essential to addressing global challenges through sustainable and reality-based solutions.